2003
DOI: 10.1109/tcst.2003.815552
|View full text |Cite
|
Sign up to set email alerts
|

An H-infinity-based control design methodology dedicated to the active control of vehicle longitudinal oscillations

Abstract: International audienceThis paper deals with the problem of active damping of vehicle oscillations. A complete methodology based on an H∞ optimization is presented. Several dedicated analysis tools are used in order to analyze the behavior of the closed-loop system. Two tuning parameters allow the design of a controller managing the compromise between performance (in terms of oscillation attenuation and limit cycles) and robustness. Finally, a feedforward component is designed in order to improve the performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…sizes n, p and q n = 10, p = 11, q = 1 n = 12, p = 1, q = 25 n = 60, p = 28, q = 14 n = 3, p = 1, q = 4 1 − ρ(A) • The first example comes from Control Theory: the LTI system is extracted from an active controller of vehicle longitudinal oscillation [11], and WCPG matrix is used to determine fixed-point arithmetic scaling of the states and the output.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…sizes n, p and q n = 10, p = 11, q = 1 n = 12, p = 1, q = 25 n = 60, p = 28, q = 14 n = 3, p = 1, q = 4 1 − ρ(A) • The first example comes from Control Theory: the LTI system is extracted from an active controller of vehicle longitudinal oscillation [11], and WCPG matrix is used to determine fixed-point arithmetic scaling of the states and the output.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…Subsequent research has shown that there are still many researchers investigating active control for drivetrain vibrations by controlling engine torque output actively and dynamically with feed forward control method [9], optimal algorithm [10,11], model predictive control [12,13], H-infinity optimization [14] to replace the simple open-loop system to reduce oscillation when shifting or during tip in/out. The core principles of the above concepts are similar, by controlling engine torque according to drivetrain motion state, a controller will compensate for the speed oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…The method is robust with respect to modeling errors and parametric uncertainties. A combined H ∞ feedback and feedforward control is empoyed to damp out longitudinal oscillations using µ analysis in Lefebvre et al (2003) . The robust H ∞ method is compared to the Linear Quadratic Regulator design in Junaid et al (2005).…”
Section: Introductionmentioning
confidence: 99%